Antibiotic allergy labels and optimal antimicrobial stewardship. Issue 3 (20th March 2022) - Chakravorty, Arindam; Binder, Elene; Rawlins, Matthew; Trevenen, Michelle; Ingram, Paul R.; McKeogh, Anna; Murray, Kevin; Dyer, John; Lucas, Michaela
Abstract: Background: Although common, antimicrobial allergy labels (AAL) rarely reflect immunologically‐mediated hypersensitivity and can lead to poorer outcomes from alternative antimicrobial agents. Antimicrobial stewardship programs are ideally placed to assess AAL early as a means of improving antimicrobial use. Aims: To quantify the prevalence of AAL in patients referred for antimicrobial stewardship review and assess their impact on antibiotic prescribing, patient mortality, hospital length of stay, readmission and rates of multidrug‐resistant infections. Methods: We conducted a retrospective analysis of adult patients referred for inpatient antimicrobial prospective audit and feedback rounds (PAFR) through an electronic referral system ( eReferrals ) over a 12‐month period in 2015. Outcome data were collected for a period of 36 months following the initial review. Results: Of the 639 patient records reviewed, 630 met inclusion criteria; 103 (16%) had an AAL, of which 82 (13%) had reported allergies to β‐lactam antibiotics. Those with AAL were significantly less likely to be receiving guideline‐recommended antimicrobial therapy (50% vs 64%, P  = 0.0311); however, there were no significant difference in mortality, hospital length of stay, readmission or increased incidence of multidrug‐resistant infections. Conclusions: Our cohort demonstrated that AAL was associated with reduced adherence to antibiotic guidelines. The lack of association with adverse outcomes may reflect limitations within the study including retrospective cohort study numbers and observational nature, further skewed by high rates of poor documentation. A clear opportunity exists for antimicrobial stewardship programs to incorporate allergy assessment, de‐labelling, challenge and referral into these rounds.